A study on the potability of rural water systems in Tanah Merah and Pasir Puteh districts,Kelantan - Affandi, Sharifah Mahani Syed Mahar (2003)
BAKAS (Water supply and environmental sanitation) unit of Ministry of Health was first introduced in 1974 for controlling water and vector borne diseases by providing safe water supply and sanitation facilities for rural areas. A cross-sectional study was conducted to study the potability of rural water systems such as Gravity Feed System (GFS), Over Head Tank (OHT), Direct Connection (DC) and Air Kelantan Sdn. Bhd.(AKSB) water connections supplies by BAKAS unit in Tanah Merah and Pasir Puteh, Kelantan. A total of 325 households from different villages were selected using multistage random sampling. Data were collected using 3 methods; interviewed using structured questionnaire regarding the consumer satisfaction on the quality and the quantity of the rural water supply, water sampling for physical, chemical and microbiology, and sanitary survey to estimate the risk of water contamination. The results of the water analysis were compared with the permissible level from Ministry of Health Malaysia. Parameters that have violations are, presence E.Coli (54.3%), pH (55.2%),colour (2.5%), turbidity (29.3%), free residual chlorine (86.7%), ammonia (3.7%), iron (3.7%) and phosphate (16.7%). No violation found in conductivity, total hardness, total dissolved solid, sulphate and nitrate in all water samples. Results also shows that the most unpotable rural water system is the GFS in which all the samples taken are contaminated with E. coli. Comparing the 2 types of well system, OHT are better than DC. The most potable water system is AKSB water connection in which only 3. 8% are contaminated. Majority of the consumer (75.3%) are very satisfied with the water system although 66.2% are still complaining of not enough water supply. This is one of the worrying situations because they used alternative water sources that are usually not safe and not monitored by the MOH. Sanitary survey showed that GFS is more at risk for contamination compared with OHT and DC. Thus the water potability in Tanah Merah and Pasir Puteh is still not very satisfactory. The condition could be improved by community participation in all aspects of water supply and sanitation schemes including planning, design, construction, operation and maintenance the BAKAS projects. Health education on good personal hygiene also can help in preventing the water-borne diseases.